Perceptions of Life Balance Among a Working Population in Sweden - Wagman, P.; Bjorklund, A.; Hakansson, C.; Jacobsson, C.; Falkmer, Torbjorn (Sage Publications, Inc, 2010)
A life in balance is commonly related to health and well-being. However, our knowledge regarding the perceptions of life balance among the general population is limited. Our aim was to explore the perception of life balance among working people without recent long-term sick leave. Individual interviews were conducted with 7 men and 12 women and analyzed according to grounded theory, aiming at achieving a description. The results showed that life balance includes four interrelated dimensions: activity balance, balance in body and mind, balance in relation to others, and time balance. Life balance was regarded by the participants as health related, promoted by a sense of security, and affected by context and individual strategies. Life balance was also seen as being individually defined and dynamic. The results indicate that the perceptions of life balance might be quite general because they show similarities with previous research on different populations.